Geographical information sistem for mapping mosques in the village of Dayo Rokan Hulu District - Aldi Syahputra; Muhammad Febri Devara; Murtadho Habibi Habibi; Hadi Asnal (Computer Science and Information Technology, 2022)
Geographic Information Sistem (GIS) is a component consisting of hardware, software, human resources and data that work together effectively to enter, store, repair, update, manage, manipulate, integrate, analyze and display data in an information-based geographic [1]. This research was conducted to analyze the distribution of mosques and information about mosques in Dayo Village, Rokan Hulu District, Riau. The aim is to help the community, especially newcomers, to find maps of the distribution of mosques, routes to mosques, schedules for Friday prayer officers and other information that currently does not use a computerized sistem, which is an obstacle especially for the people in the Dayo Village area. The method used in data collection was by direct observation of mosques in Dayo Village and conducting interviews with mosque administrators and local residents, besides that a literature study was also carried out to find references to previous research. By using GIS, it is hoped that it will be easier for the community to find out the distribution of mosques in Dayo Village, the locations of the mosques along with the information available. All of this information can be easily accessed online via smartphones or other devices